2005
DOI: 10.3748/wjg.v11.i7.948
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of type II tumor suppressor gene RARRES3 in tissues of hepatocellular carcinoma and cholangiocarcinoma

Abstract: Expression of RARRES3 is positively correlated to well-differentiated CC, which supports the role of RARRES3 in malignant epithelial differentiation of the tumor. The decrease in RARRES3 expression in tissues of HCC and CC with moderate and poor differentiation suggests that altered RARRES3 expression may play a role in the carcinogenesis of the liver and biliary tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…CD38 expressed mainly in leukocytes is involved in cell adhesion and signal transduction, RARRES3 is a negative regulator of cell proliferation, whereas ECGF1 is a growth factor with angiogenic effects. RARRES3 has been reported to act as a tumor suppressor or growth regulator (46). Its decreased expression in colorectal cancer seems to support this assumption.…”
Section: Discussionsupporting
confidence: 65%
“…CD38 expressed mainly in leukocytes is involved in cell adhesion and signal transduction, RARRES3 is a negative regulator of cell proliferation, whereas ECGF1 is a growth factor with angiogenic effects. RARRES3 has been reported to act as a tumor suppressor or growth regulator (46). Its decreased expression in colorectal cancer seems to support this assumption.…”
Section: Discussionsupporting
confidence: 65%
“…15 The expression of TIG3 was decreased in most aggressive squamous cell carcinoma tumors, 7 as well as in hepatocellular carcinoma, cholangiocarcinoma and colorectal adenocarcinoma. 16 TIG3 expression is elevated after treating with tazarotene in vitro in primary human keratinocytes confirmed in our study and in vivo in psoriatic lesions, which may result in keratinocyte growth arrest, apoptosis and terminal differentiation. Treatment with all-trans retinoic acid can also induce TIG3 expression in head and neck carcinomas, lung carcinoma cells 17 and gastric cancer cells.…”
Section: Discussionsupporting
confidence: 86%
“…TIG3 mapped to chromosome 11q23 that was hypothesized to contain a tumor suppressor 15 . The expression of TIG3 was decreased in most aggressive squamous cell carcinoma tumors, 7 as well as in hepatocellular carcinoma, cholangiocarcinoma and colorectal adenocarcinoma 16 . TIG3 expression is elevated after treating with tazarotene in vitro in primary human keratinocytes confirmed in our study and in vivo in psoriatic lesions, which may result in keratinocyte growth arrest, apoptosis and terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that overexpression of RIG1 suppressed the colonies formation in T47D and HaCaT cells [1,6]. Compare to normal cells, the expression of RIG1 was decreased in many human cancer specimens [7–9]. RIG1 has also been shown to facilitate apoptosis and the terminal stages in keratinocyte differentiation via activation of type I transglutaminase [6].…”
Section: Introductionmentioning
confidence: 99%